THE EFFECT OF THE USE OF MARGARINE AND BUTTER WITH DIFFERENT PERCENTAGES ON THE QUALITY OF SESAME MILK PIE - Hasna Nafisah; Ridawati Ridawati; Mutiara Dahlia (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to determine the effect of using margarine and butter with different percentages on the physical and sensory qualities of sesame milk pies. The experimental method was carried out by differentiating the percentages of margarine and butter, namely 75%: 25%, 50%: 50%, and 25%: 75%. Physical quality was analyzed using the Anova test and sensory quality was analyzed using the Kruskal Wallis test with a significant level of =0.05. Physical quality in terms of diameter and weight did not show a significant effect. Physical quality in the aspect of inner thickness showed a significant effect with the highest yield on sesame milk pie 25%:75% with an increase of 40.53%, second on sesame milk pie 50%:50% with an increase of 38.10%, and the lowest 75 %:25% with an increase of 31.64%. Sensory quality in the aspect of crust color, deep color, milk aroma, and trigeminal showed no significant effect. Aspects of brittleness, softness, sweetness, and savory showed a significant influence. The friability aspect with the highest value of 3.53 (not brittle) at 75%:25% product, the second 3.07 (slightly brittle) at 50%:50% product, and the lowest 2.47 (brittle) in 25%:75 product %. The softness aspect with the highest value 4.25 (very soft) on the 25%:75% product, the second 3.53 (soft) on the 50%:50% product, the lowest 3.33 (slightly soft) on the 75%:25 product . Aspects of sweetness with the highest value 4.53 (sweet) in the product 25%:75% and 50%:50%, the lowest value 3.6 (slightly sweet) in the product 75%:25. Aspects of savory taste with the highest value of 4.53 (savory) on products 75%:25, and the lowest value of 3.8 (slightly savory) on products of 50%:50% and 25%:75%. Based on the results of the highest assessment of the sesame milk pie with the best quality, the ratio of margarine and butter is 25%:75%